Impact of COVID-19 transmission rate on co-movement of China’s stock markets - Xiao, Hongfei; Lin, Deqin; Zhang, Zhaowei (Frontiers in Applied Mathematics and Statistics, 2025)
IntroductionThis paper explored the impact of COVID-19 transmission rate on co-movement of China’s stock markets.MethodsBy employing the rolling time series model to measure the COVID-19 transmission rate and DCC-GARCH model to analyze co-movement of China’s Stock markets, this paper managed to demonstrate a significant correlation between COVID-19 transmission rate and co-movement of China’s stock markets.ResultsThe findings revealed that co-movement of China’s stock markets was significantly affected by the COVID-19 transmission rate during the pandemic period. As the transmission rate accelerated, the co-movement among China’s stock markets intensified, indicating that the shock of the pandemic strengthened their interconnectedness, leading to a broader spread of risk.DiscussionThis result suggests that the pandemic shock not only impacted individual stock markets but also intensified the correlations and risk spillovers among them. Such findings have important implications for investors, policymakers, and regulators. Therefore, during the virus outbreak stage, attempting to diversify risk by investing funds into different stock markets is ineffective; a more viable strategy to minimize losses would be to sell their held stocks. For policymakers, promptly introducing and effectively implementing virus prevention and containment measures is a feasible approach to mitigate the epidemic’s impact on domestic financial markets and stabilize their development.